Li-ion battery from industrial waste water - Nor Azlin, Yah; Rohana, Abu (2021)
Inpregnating Ag into BC has shown good antimicrobial properties. But, it affect the properties of BC such as WHC and WRR. To investigate the water holding and release properties of BC-AgNPs.